مشكلات لطلاب الفصل السادس في تعلّم مادة اللغة العربية ومحاولة المدرّسين في حلّها بمدرسة الإبتدائية بيت القرآن كونتور العام الدراسي: 2017-2018 - Dita Retno Safitri; Puput Wahyu Nurmasanti (AL-ASASIYYA: Journal Of Basic Education, 2018)
Arabic is the language in which Arabs express their purpose. The Institute of the House of Quran Contour of the Institute of Education and advocacy, which founded on the establishment of Quran and Sunnah Prophet peace be upon him. The elementary school was one of the elementary schools that teaches and learns Arabic language lessons. Many of his professors and professors graduated from institutes in Indonesia so that they could speak Arabic. In this case, the teachers and teachers were also taught to their students so that the environment of the school environment of the Arabic language. The pupils do not feel strange in Arabic. Problems in learning the Arabic language are difficulties in learning, and sometimes it may appear that some students do not understand the difficult vocabulary and methods considered. As if they are difficult to change the style. These difficulties lead to their difficulty in deriving the deductions from the specific topic in the reading lesson. And because the students of the sixth grade in the primary school of beginners in the study of the Arabic language, and this holds them to the difficulty in the composition of words.